Volume 4: Heat Transfer, Parts a and B 2012
DOI: 10.1115/gt2012-68405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endwall Contouring on a Transonic Turbine Blade Passage: Part 2—Heat Transfer Performance

Abstract: Contouring of turbine endwalls has been widely studied for aerodynamic performance improvement of turbine passages. However, it is equally important to investigate the effect of contouring on endwall heat transfer, because a substantial increase in endwall heat transfer due to contouring will render the design impractical. In this paper, the effect of contouring on endwall heat transfer performance of a high-turning HP-turbine blade passage, operating under transonic exit Mach number conditions, is reported. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Saha and Acharya [16] computationally evaluated nine endwall shapes and found that the best design reduced overall heat transfer by 8%, with significant reductions of over 300% near the suction side (SS) leading edge and approximately 20% in the throat compared to a flat endwall. Panchal et al [17] also found reductions in local and endwall-average heat transfer at high subsonic conditions for contoured endwalls, attributed to redirection of the passage vortex with contouring. A contour studied by Lynch et al [18] (same as in this study) significantly decreased endwall heat transfer near the PS of the passage relative to a flat endwall, which was attributed to reduced strength of the passage vortex.…”
Section: Relevant Past Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Saha and Acharya [16] computationally evaluated nine endwall shapes and found that the best design reduced overall heat transfer by 8%, with significant reductions of over 300% near the suction side (SS) leading edge and approximately 20% in the throat compared to a flat endwall. Panchal et al [17] also found reductions in local and endwall-average heat transfer at high subsonic conditions for contoured endwalls, attributed to redirection of the passage vortex with contouring. A contour studied by Lynch et al [18] (same as in this study) significantly decreased endwall heat transfer near the PS of the passage relative to a flat endwall, which was attributed to reduced strength of the passage vortex.…”
Section: Relevant Past Studiesmentioning
confidence: 93%
“…The linear cascade ( Fig. 1(b)) contained seven blades based on a low-pressure turbine airfoil geometry that has been studied extensively in the literature, particularly with regards to nonaxisymmetric endwall contouring [14][15][16][17][18][19]. Table 1 lists the geometrical parameters and operating conditions for the cascade.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Many studies have focused on aerodynamic optimization (reduced exit flow angle deviation [3,4], or reduced total pressure loss [5,6]). Endwall heat transfer performance has also been considered as a driving metric [7,8]. In most cases, experiments indicate that an aerodynamically optimized endwall also has improved heat transfer performance ( [7,9]).…”
Section: Relevant Past Studiesmentioning
confidence: 99%
“…Endwall heat transfer performance has also been considered as a driving metric [7,8]. In most cases, experiments indicate that an aerodynamically optimized endwall also has improved heat transfer performance ( [7,9]). Many other studies have demonstrated the effectiveness of contouring in rig and engine environments (e.g., [10,11]).…”
Section: Relevant Past Studiesmentioning
confidence: 99%